Do empowered individuals make healthier food choices? An experimental analysis of men's and women's food choices among smallholder farming households in Guatemala - Arora, Diksha (International Center for Tropical Agriculture, 2019)
Presented by Diksha Arora (International Center for Tropical Agriculture), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.